Radiographic evaluation of mandibular morphometric differences in prepubertal and postpubertal individuals in a Turkish subpopulation - Burak Kerem Apaydin; Hilal Ozbey (Wolters Kluwer Medknow Publications, 2020)
Introduction: Radiologic differences in the mandible between genders have been evaluated; however, studies are lacking in comparison of prepuberty and postpuberty. The purpose of this study was to measure the gonial angle (GA), ante GA (AGA), bicondylar breadth (BB), mental index (MI), minimum ramus breadth (MRB), bigonial width (BW), and ramus height (RH) on panoramic radiographs obtained from Turkish patients and to elucidate how those measurements relate with age and gender in pre- and post-pubertal period. Materials and Methods: Panoramic radiographs of patients aged between 5 and 50 years old were taken according to the manufacturer's instructions. A total of 760 radiographic images were evaluated (19 groups, n = 40). GA, AGA, BB, MI, MRB, BW, and RH values were measured on digital panoramic radiographs using Java Image Processing Software on the images. The data were analyzed by independent sample t-tests and regression analysis using a software program (P < 0.05). Results: Only AGA values were statistically significant between male and female patients in both prepubertal and postpubertal periods (P < 0.05). A statistically significant difference was found in AGA, BB, MI, MRB, BW, and RH in postpubertal period between male and female patients (P < 0.05). Besides, when the ages between 5 and 20 years were analyzed, all parameters except for GA and AGA were significantly correlated positively with age in both genders. Conclusions: Only AGA values can be used for gender determination both in prepubertal and postpubertal period. In addition, BB, MI, MRB, BW, and RH values were correlated positively with age in both prepubertal and postpubertal groups.